2019
DOI: 10.24326/asphc.2019.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1-Methylocyclopropene (1-McP) on the Quality and Storability of ‘Red Jonaprince’ Apples Stored in Different Conditions

Abstract: The research was carried out on apples of the cultivar ‘Red Jonaprince’ in two storage seasons of 2015/2016 and 2016/2017. Both 1-MCP-treated and untreated apples were stored for 120 and 150 days at 2°C and 90–92% relative humidity in a regular cold store (NA) and in two atmospheric controlled storages, i.e. 2% CO2 and 2% O2 (CA) and 2% CO2 and 1.2% O2 (ULO). Apples were evaluated directly after the storage and after 7 days of simulated shelf-life. It was shown that storage conditions had significant impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…'Conference' pears harvested on the optimal harvest date can be kept for 2 to 4 months in an ordinary cold store and for about 6 months in a CA cold store [31]. Various modern types of cold stores with a controlled atmosphere in which fruit metabolism is maintained on the verge between aerobic and anaerobic respiration as well as the use of substances that slow down the ripening processes, such as 1 MCP, allow one to extend the fruit storage period [32,33], but cannot correct the negative effects of too early or too late harvest. In such cases, even the best technology will not improve fruit quality after a few months [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…'Conference' pears harvested on the optimal harvest date can be kept for 2 to 4 months in an ordinary cold store and for about 6 months in a CA cold store [31]. Various modern types of cold stores with a controlled atmosphere in which fruit metabolism is maintained on the verge between aerobic and anaerobic respiration as well as the use of substances that slow down the ripening processes, such as 1 MCP, allow one to extend the fruit storage period [32,33], but cannot correct the negative effects of too early or too late harvest. In such cases, even the best technology will not improve fruit quality after a few months [2].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that fruit firmness gradually decreases during ripening due to progressive enzymatic degradation of cell wall polymers, alteration in cell wall structure caused by degradation processes (e.g., polygalacturonase) and also polysaccharide degradation, which leads to the breakdown of starch, cellulose and hemicellulose. These changes result in a loss of integrity of the middle lamella, which is rich in pectins that control cell-to-cell adhesion, thus influencing the texture of the fruit [7,33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…The firmness was assessed according to a previously described method [31] removing the peel, the firmness was measured in duplicate for each sample. Each urement was conducted for opposite sides of the apple.…”
Section: Measurementsmentioning
confidence: 99%
“…The 1-MCP treatments resulting in delayed fruit ripening and the success of 1-MCP technology for apples is associated with the fact that for the apple, the maintenance of 'at harvest' quality is needed and only a moderate softening texture is desirable [29]. Such treatment for 'Red Jonaprince' is commonly applied during storage (postharvest), and such treatment has been shown to delay softening [31]. However, recently, its preharvest application has also been studied and it was indicated that it may allow delayed harvesting and reduce the quality deterioration during storage [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among promising options to apply is the use of 1-Methylcyclopropene (1-MCP) during storage (postharvest), which has been proven to delay the softening of Red Jonaprince apples [11]. However, the 1-MCP was studied in the preharvest period as a novel option to maintain the eating quality [12] and enable delayed harvesting [13].…”
Section: Introductionmentioning
confidence: 99%